PENERAPAN METODE KONSTRUKTIVISME PADA MATA PELAJARAN MENULIS PUISI SISWA KELAS X BISNIS DARING DAN PEMASARAN SMK NEGERI 5 KOTA JAMBI - Monalisa Senangta Purnama Sari; Rasdawita Rasdawita; Hilman Yusra (Universitas Muhammadiyah Purwokerto, 2023)
This researcher is entitled Application of Constructivism Method in Poetry Writing Subject for Class X Online Business and Marketing (BDP1) SMK Negeri 5 Jambi City. This study uses a descriptive type of research with a qualitative approach. The subjects of this study were students of class X BDP1 SMK N 5 Jambi City. Data collection techniques in the form of performance tests, FGD (Forum Group Discussion) and documentation. The results of this study indicate that the teacher has problems in controlling students' assertiveness. A student does not want to do the assigned task. This is a shortage of teachers in the firmness of the rules at the beginning of learning. But in the end, the student did the task given by the teacher. Overall the teacher is able to provide an exciting atmosphere in learning which has an impact on students' comfort in learning, visualization and simple language in this method also make it easier for students to understand the learning material. The teacher did not find any significant obstacles in the application of this method.